The Appearance and Disappearance of Exocomet Gas Absorption - Barry Y. Welsh; Sharon L. Montgomery (Advances in Astronomy)
CaII K-line (3933 Å) absorption profiles observed towards 15 A-type and two B-type stars with known (or suspected) debris disks, in addition to archival spectral data for three A-type stars, are presented. Inspection of the extracted CaII K-line absorption lines has determined that one late B-type (HD 58647) and four new A-type (HD 56537, HD 64145, HD 108767, and HD 109573) stellar systems exhibit short-term (night-to-night) absorption variation within these profiles. This variability is due to the liberation of gas from falling evaporating bodies (the so-called FEBs activity) on the grazing approach of exocomets towards their parent star. Also we present archival spectra of the FeI λ3860 Å and CaII K-lines towards β Pictoris (HD 39060) that, for the first time, reveal the absorption signatures of FEB activity at similar velocities in both line profiles. FEB-hosting stars seem to be of an earlier type (on average spectral type Al.8 as compared with A3.1) than those where no FEB activity has been observed. This could be due to stellar activity levels (such as chromospheric activity or nonradial pulsations) being of a higher level within the atmospheres of these hotter A-type stars.